Formação continuada de professores (as) na educação infantil: contribuições para uma educação antirracista a partir das tertúlias dialógicas pedagógicas - Guedes, Helenice Aparecida Magalhães De Sousa (2024)
The thesis discusses the Dialogic Pedagogical Training of Teachers and its contributions to Anti-Racist Education, with a focus on Early Childhood Education. This approach is recognized as a Successful Educational Action, identified by the Includ-Ed project (2011). Based on the Communicative Methodology (CM), the main objective of the research was to analyze, through transformative and/or exclusionary elements reported by the research participants, how the continued education of Early Childhood teachers can contribute to Anti-Racist Education, with dialogic pedagogical gatherings as the central axis. The study aims to identify its contributions to anti-racist education and compliance with related laws, 10.639/03 and 11.645/08. The central thesis argues that Dialogic Pedagogical Gatherings are a tool that provides effective knowledge and instruments for the continued education of teachers to promote Anti-Racist Education. To this end, Dialogic Pedagogical Gatherings on Anti-Racist Education were conducted with in-service teachers and school staff through a course offered and certified by institutional means, in partnership with the research center to which the researcher belongs. The guiding questions of this study are: What knowledge do teachers have about Anti-Racist Education? What transformative and exclusionary elements do Dialogic Pedagogical Gatherings (DPG) offer Early Childhood teachers for the development of Anti-Racist Education? Data collection and organization were carried out through three instruments: Questionnaires, Communicative Interviews, and Communicative Discussion Groups (Gómez, 2006). The research involved 18 participants, including in-service teachers and members of the management team from two public municipal schools. The results indicate that dialogic pedagogical training, through DPGs, can contribute to promoting Anti-Racist Education and strengthening the ethnic and racial identity of children. For this, it is necessary to expand the inclusion of the topic in continued training and carry it out base on scientific evidence.